2010
DOI: 10.4236/ti.2010.11007
|View full text |Cite
|
Sign up to set email alerts
|

How to Support Innovative Behaviour?The Role of LMX and Satisfaction with HR Practices

Abstract: Innovative behaviour of employees refers to a key aspect of organizational effectiveness: the creation, intro-duction and application of new ideas within a group or organization in order to benefit performance. Using data from a Dutch and German survey in four technical organizations (n=272) we developed and tested two models to explain the relationships between Leader-Member-Exchange (LMX), satisfaction with HR prac-tices (employee influence, flow, rewards and work content) and innovative behaviour. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 38 publications
5
137
1
7
Order By: Relevance
“…In organizations supervisors are viewed as the direct agent of organizations (Sanders et al, 2010) and any actions of the supervisor are viewed as the actions of the organization (Eisenberger, Huntington, Hutchinson & Sowa, 1986). Thus favorable actions by the supervisor will encourage employees to engage in expected behavior such as innovativeness (Sanders et al, 2010). A study by Janssen and Van Yperen (2004) based on 170 employees from an energy supplier found a positive impact of LMX on IWB.…”
Section: Leader-member Exchange and Iwbmentioning
confidence: 99%
See 2 more Smart Citations
“…In organizations supervisors are viewed as the direct agent of organizations (Sanders et al, 2010) and any actions of the supervisor are viewed as the actions of the organization (Eisenberger, Huntington, Hutchinson & Sowa, 1986). Thus favorable actions by the supervisor will encourage employees to engage in expected behavior such as innovativeness (Sanders et al, 2010). A study by Janssen and Van Yperen (2004) based on 170 employees from an energy supplier found a positive impact of LMX on IWB.…”
Section: Leader-member Exchange and Iwbmentioning
confidence: 99%
“…This is because employees view the existence of distribution equity with regards to the rewards thus encouraging them to engage in IWB greater (Sanders, Moorkamp, Torka, Groenveld & Groenveld, 2010). In organizations supervisors are viewed as the direct agent of organizations (Sanders et al, 2010) and any actions of the supervisor are viewed as the actions of the organization (Eisenberger, Huntington, Hutchinson & Sowa, 1986). Thus favorable actions by the supervisor will encourage employees to engage in expected behavior such as innovativeness (Sanders et al, 2010).…”
Section: Leader-member Exchange and Iwbmentioning
confidence: 99%
See 1 more Smart Citation
“…The reward itself can promote intrinsic motivation of the employees. However, the author found that, although the behaviour of giving rewards to the employees was found to be related to innovativeness [15], [18], [19], Sanders [20] have proven vice versa; rewarding has no positive correlation with innovativeness.…”
Section: A Relationship Between Leadership Practices and Innovative mentioning
confidence: 99%
“…The literature contains various researches studying the determinants of innovative behavior from organizational, individual and contextual angles (Mumford et al, 2002;Sanders et al, 2010;Taştan, 2013). One of the leading works, the study by Hurt et al (1977) investigated individual innovative behaviors from a personality perspective using generalized desire to change.…”
Section: Innovative Behaviormentioning
confidence: 99%